THE ANALYSIS OF FRONT OFFICE DEPARTMENT SERVICE QUALITY FOR CUSTOMER’S SATISFACTION AT PADMA RESORT LEGIAN - Ni Luh Putu Mira Indah Pratiwi; I Gusti Made Wendri (Journal of Applied Sciences in Travel and Hospitality, 2019)
The purpose of this research is to know there is a gap between the guest’s perception and guest’s expectation to the Front Office Department service quality at Padma Resort Legian, and to know which indicators need to be improved and maintained to enhance the service quality of Front Office Department for customer’s satisfaction at Padma Resort Legian. The data used in this research are quantitative data which are collected from observation, literature study, questionnaire with validity and reliability tested and secondary data. The total of respondents are 60 respondents using incidental sampling method. Data analysis technique used is the SERVQUAL Method and Importance-Performance Analysis applied in Cartesian Diagram. The result of this research is show that there are negative and positive gap between perceptions and expectations. The result of the Importance-Performance Analysis found 1 indicator on Quadrant A which as the major weakness and need improvement which is the attributes number 4, fast and properly service of check-in and check-out process by the Front Office Staff. On the other hand, there are 6 indicators on Quadrant B which as the major strengths and opportunities. Padma Resort Legian should immediately improve the performance of indicator on Quadrant A to reach customer’s satisfaction.